ANALISIS PENDAPATAN USAHATANI JERUK SIAM (Citrus nobilis) DAN KONTRIBUSINYA TERHADAP PENDAPATAN PETANI (Studi Kasus Di Desa Sekoci Kecamatan Besitang Kabupaten Langkat) - Putri Rahayu; Silvia Anzitha; Cut Gustiana (Bajang Institute, 2023)
This study aims to analyze how the level of income and the level of contribution received by Siamese orange farmers in running their farming. This research was conducted in Sekoci Village, Besitang District, Langkat Regency. This study uses farming analysis methods, namely analyzing production costs, revenue and income of Siamese citrus farming and analyzing the contribution of Siamese citrus farming to farmers' income. Based on the results and discussion of the research, it can be concluded that the production cost of Siamese orange farming in Sekoci Village is Rp.12,316,597.93/year, the total revenue obtained from Siamese orange farming is Rp.40,733,350/Year and the Siamese orange farming income is Rp.28,416,752.1/Year. Meanwhile, the average income of farmers from all Siamese citrus farming income and non-siam citrus farming income is Rp.55,096,752.1/year, so that the contribution value of Siamese orange farming is 51.5%, which means Siamese orange farming in the village. Lifeboats contribute to farmers' income